Answer:
Explanation:
We have given:
-2x+y=4 ---------equation1
3x+4y=49 ---------equation 2
We will solve the 1st equation for y and substitute the value into the 2nd equation.
-2x+y=4 ---------equation1
Move the values to the R.H.S except y
y = 2x+4
Now substitute the value of y in 2nd equation:
3x+4y=49
3x+4(2x+4)=49
3x+8x+16=49
Combine the like terms:
3x+8x=49-16
11x=33
Now divide both the sides by 11
11x/11 = 33/11
x= 3
Now substitute the value of x in any of the above equations: We will substitute the value in equation 1:
-2x+y=4
-2(3)+y=4
-6+y=4
Combine the constants:
y=4+6
y = 10
Thus the solution set of (x,y) is {(3,10)}....